The South African Christian story as conflict within us and quarrel amongst us - Penxa-Matholeni, Nobuntu (Stellenbosch Theological Journal, 2023)
This article delves into the origins and extent of racial conflicts within and among us as South African Christians, questioning whether they arise from a flawed foundation. Employing an indigenous storytelling methodology, this article aims to uncover these quarrels and their impact on the church, academy, and society. Central to our exploration is the endleleni metaphor, meaning “on the road,” which will be defined to dismantle the divisive hierarchized foundation and foster a new interconnected foundation rooted in our shared humanity. Ultimately, the metaphor of endleleni lights the path towards a promising future.